'At the crossroads towards polyploidy': genomic divergence and extent of homoploid hybridization are drivers for the formation of the ox‐eye daisy polyploid complex (Leucanthemum, Compositae‐Anthemideae). Issue 4 (5th April 2019) - Wagner, Florian; Ott, Tankred; Zimmer, Claudia; Reichhart, Verena; Vogt, Robert; Oberprieler, Christoph
Summary: Polyploidy plays a paramount role in phytodiversity, but the causes of this evolutionary pathway require further study. Here, we use phylogenetic methods to examine possible polyploidy‐promoting factors by comparing diploid representatives of the comprehensive European polyploid complex Leucanthemum with members of its strictly diploid North African counterpart Rhodanthemum . We investigate genetic divergence and gene flow among all diploid lineages of both genera to evaluate the role of genomic differentiation and hybridization for polyploid speciation. To test whether hybridization in Leucanthemum has been triggered by the geological conditions during its diversification, we additionally generate a time‐calibrated phylogeny of 46 species of the subtribe Leucantheminae . Leucanthemum shows a significantly higher genetic divergence and hybridization signal among diploid lineages compared with Rhodanthemum, in spite of a similar crown age and diversification pattern during the Quaternary. Our study demonstrates the importance of genetic differentiation among diploid progenitors and their concurrent affinity for natural hybridization for the formation of a polyploid complex. Furthermore, the role of climate‐induced range overlaps on hybridization and polyploid speciation during the Quaternary is discussed. Abstract : See also the Commentary on this article by Stuessy & Weiss‐Schneeweiss, 223 : 1690–1692 .